Technology, Teen Dating Violence and Abuse, and Bullying in Three States, 2011-2012 - Zweig, Janine ([Verlag nicht ermittelbar], 2015)
This project examined the role of technology use in teen dating violence and abuse, and bullying. The goal of the project was to expand knowledge about the types of abuse experiences youth have, the extent of victimization and perpetration via technology and new media (e.g., social networking sites, texting on cellular phones), and how the experience of such cyber abuse within teen dating relationships or through bullying relates to other life factors. This project carried out a multi-state study of teen dating violence and abuse, and bullying, the main component of which included a survey of youth from ten schools in five school districts in New Jersey, New York, and Pennsylvania, gathering information from 5,647 youth about their experiences. The study employed a cross-sectional, survey research design, collecting data via a paper-pencil survey. The survey targeted all youth who attended school on a single day and achieved an 84 percent response rate.